In Vitro ANTITRYPANOSOMAL ACTIVITY OF CAMPESTEROL AND ETHYL OLEATE FROM THE METHANOL EXTRACT OF Abrusprecatorius Linn - ABUBAKAR AHMAD, KHADIJAH; AMINU MUHAMMAD; AHMAD, GARBA; MAIKUDI IDRIS, MUSA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Abrusprecatorious (fabaceae) is an important medicinal plant used to treat tetanus, rabies, fever, and jaundice. The plant was investigated in present research for the presence of secondary metabolites, and the antitrypanosomal activity against Trypanosomes bruceibrucei for the development of new and cost effective alternative strategies for the treatment of trypanosomiasis. The plant was air dried and extracted with organic solvent in a polarity gradient of petroleum ether, ethyl acetate and methanol. The column chromatographic CC of the methanol extracts leads to the isolation of campesterol and ethyl oleate which were characterized using Fourier transform Infra – red FT-IR, Gas Chromatography mass spectrometry GC-MS and Nuclear Magnetic Resonance NMR analysis and comparison with literature data. An appreciable in vitroantitrypanosomal activity was attained by the campesterol and ethyl oleate by drastically reducing the motility rate of the Trypanosomes bruceibruceiat a concentration of 50 mg/ml within 80 and 110 minutes respectively. These results suggest that the plant contain potent antitrypanosomal activity agents that could be developed as drugs for African animal trypanosomiasis and also shows the ethno – pharmacological usefulness of the plant